Donor‐/Acceptor‐Substituted Tetrakis(arylethynyl)benzenes: The Influence of Donor Group on Optoelectronic Properties. Issue 9 (12th June 2019) - Nojo, Wataru; Reingold, I. David; Bard, Jeremy P.; Chase, Daniel T.; Deng, Chun‐Lin; Haley, Michael M.
Abstract: We have prepared nine structural isomers of a tetrakis(arylethynyl)benzene chromophore functionalized with 4‐butoxyphenyl and pyridyl units as the respective donor and acceptor units and examined their steady‐state spectroscopic parameters to study how small structural variations effect the electronic absorption and emission spectra. Unlike their 4‐dibutylaminophenyl congeners that exhibited dynamic hypsochromic or bathochromic shifts in response to Lewis and Brønsted acids, the current class of compounds simply showed quenched fluorescence upon protonation; only AlCl3 elicited a red‐shifted fluorescence response. Computational studies of each system were also performed to provide additional insight into the energy levels and electronic transitions present. Abstract : Subtle but important : Nine tetrakis(arylethynyl)benzene chromophores possessing 4‐butoxyphenyl and pyridyl units as the respective donor and acceptor groups have been synthesized, and their steady‐state spectroscopic parameters investigated to learn the effects of small structural variations on the electronic absorption and emission spectra.